GREGARINES OF NUMEROUS OF СARABID BEETLES FAUNA SPECIES IN THE CENTRAL PART OF UKRAINE’S STEPPE ZONE - Kobeza, P.A.; Pakhomov, A.E. (World of Medicine and Biology, 2019)
The article presented analyzes of the main species composition of the apicomplex parasites of the gastrointestinal tract of six mass species of Carabidae in the central part of the steppe zone of Ukraine. The following species were selected for the study: Calathus ambiguus (Paykull, 1790), Calathus fuscipes (Goeze, 1777), Calathus melanocephalus (Linnaeus, 1758), Pterostichus melanarius (Illiger, 1798), Pterostichus melas (Creutzer, 1799), Pterostichus niger (Schaller, 1783). The article describes the parasitization of four types of gregarin. Identified gregarines that belong to two taxa Actinocephalidae and Gigaductidae. Gregarine species: Actinocephalus echinatus (Wellmer, 1911), Ancyrophora gracilis (Léger, 1892), Gigaductus elongatus (Moriggi, 1943), Gigaductus exiguus (Wellmer, 1911). In a scientific article used 15 literary sources, of which 9 foreign articles. The work includes 1 table of characteristics of the level of invasion by protists for common species of ground beetles. The scientific article provides micrographs of all life forms of parasites. Mass species of obligate apicomplexes of parasites in the central part of the steppe zone of Ukraine revealed two types of gregarin for six species of ground beetles: Gigaductus elongatus (Moriggi, 1943) and Gigaductus exiguus (Wellmer, 1911). Two maximum levels of invasion were detected. The first high level of invasion was detected for Calathus melanocephalus, a characteristic parasite Gigaductus exiguus. In the course of the research, 25.44% of the total number of individuals represented in the sample of the imago was found. The second maximum level of invasion is observed for the species Pterostichus melas, a typical parasite G. exiguus, which is 33.33% of the total amount of population. Differences between qualitative and quantitative characteristics between females and males are not observed. The publication uses 15 literary sources, including 9 foreign articles. The work includes a table of characteristics of the level of invasion of the simplest parasites for mass species of carbohydrates. The work contains microphotographs of all life forms of parasites. Parasites, which dominate among the six mass species of ground-beetles in the territory of the central part of the steppe zone of Ukraine, revealed two types of gregarins: Gigaductus elongatus (Moriggi, 1943) and Gigaductus exiguus (Wellmer, 1911).